2013
DOI: 10.1590/s1415-790x2013000300019
|View full text |Cite
|
Sign up to set email alerts
|

Trends of chronic health effects associated to pesticide use in fruit farming regions in the state of Ceará, Brazil

Abstract: The lower valley of Jaguaribe has registered, since the XXI century, the arrival of transnational and regional companies, which led to deep transformations in this region. The increased use of the pesticides is one of the most important ones, being able to cause alterations in human procreation and leading to congenital deformations, besides premature birth and low weight newborns. This article is an ecological study related to the period from 2000 to 2010 in the population of some cities in the state of Ceará… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 11 publications
(12 reference statements)
0
19
0
12
Order By: Relevance
“…Today, more than ten years after Gonzaga's study, it can be seen that acute pesticide intoxication is still a public health problem to be overcome in the region. 17 In our research, the main symptoms of acute intoxications reported by participants were dizziness, headache and nausea. These findings are in agreement with Taveira and Albuquerque (18) who, when analyzing a pesticides use database, showed symptoms of dizziness and nausea, among others, to be the most reported in the Brazilian state of Paraná.…”
Section: Discussionmentioning
confidence: 63%
“…Today, more than ten years after Gonzaga's study, it can be seen that acute pesticide intoxication is still a public health problem to be overcome in the region. 17 In our research, the main symptoms of acute intoxications reported by participants were dizziness, headache and nausea. These findings are in agreement with Taveira and Albuquerque (18) who, when analyzing a pesticides use database, showed symptoms of dizziness and nausea, among others, to be the most reported in the Brazilian state of Paraná.…”
Section: Discussionmentioning
confidence: 63%
“…However, the possibility of impact in environmental, plant and animal health cannot be ruled out, as some of these substances have been indicated as likely compounds of mutagenic action and endocrine disruption. In addition, studies demonstrate that chronic exposure to pesticides can promote deleterious effects on nontarget organisms and even on human populations (BURILLO-PUTZE et al, 2014;OLIVEIRA et al, 2014;RIGOTTO et al, 2013;COSTA;TEIXEIRA, 2012;SOUZA, 2000). It is also important to highlight that the samplings were punctual, and the treated water samples do not represent the spring water in these cases, once water treatment can cause desorption of the pesticides that could be adhered to the sediment.…”
Section: Resultsmentioning
confidence: 99%
“…Na empresa em que trabalhou VMS, 48,0% dos trabalhadores examinados apresentaram alterações laboratoriais das provas hepáticas (TGO, TGP, Gama GT, FA, bilirrubinas) (ALEXANDRE; RIGOTTO; PESSOA, 2011). Em relação às neoplasias, Rigotto et al (2013), ao realizarem uma análise dos dados secundários referentes a esse agravo, evidenciaram um aumento de 38% na taxa de mortalidade por câncer nos municípios de Limoeiro do Norte, Quixeré e Russas, em comparação com outros 12 municípios em que predomina a agricultura familiar, nos quais não há uma utilização intensiva de agrotóxicos como nos primeiros.…”
Section: O Modelo De Desenvolvimento Agrí-cola No Semiáridounclassified